People and biodiversity policies: Impacts, Issues and Strategies for Policy Action - Bagnoli, Philip (OECD Publishing, 2008)
The implementation of biodiversity policies will often benefit different groups to a greater or lesser degree. For example, in establishing a property right to facilitate management of a biodiversity-related resource, people who previously had unrestricted use will be adversely affected. Combining analysis and a wealth of case studies, this book offers concepts and tools for addressing distributive issues in biodiversity policy. It will help policy makers put together strategies for anticipating distributive impacts across different groups; and for selecting processes and instruments that manage distributive impacts without compromising conservation and use objectives.
Keywords: Verteilung; Wohlfahrtseffekt; Effizienz; Umweltpolitik; Naturschutz; Biodiversität